Accumulation of cadmium and zinc in barley regenerants on a provocative soil background with cadmium - O. N. Shupletsova; E. V. Tovstik (Труды по прикладной ботанике, генетике и селекции)
Background. An effective way to obtain barley (Hordeum vulgare L.) genotypes stress-tolerant to cadmium, with a low level of toxic ion accumulation in grain, is the selection of cells in selective in vitro systems, based on somaclonal variability, which promotes the formation of specific and nonspecific adaptive mechanisms.Materials and methods. The object of the study was cv. ‘999-93’, developed by selection from a hybrid combination of spring barley (Luly × Conrad) × 2867-80, and its regenerated forms in seed reproductions of the 3–5th generation, induced in the process of cell selection on media with cadmium, aluminum and polyethylene glycol. The plants were grown under normal soil conditions and against a provocative background for cadmium.Results. The contribution of the environment-forming activity in the roots of the studied genotypes to inactivation of toxic ions appeared insignificant. The total removal of cadmium by plants against a provocative background increased 22.5 times, reaching 5.8–10.3 mg/kg of dry phytomass when distributed among organs: roots (91.9–93.4%) > stems (5.9–7.8%) > grain (0.5–0.8%). The amount of toxic metal in grain increased 11 times in the original form and 2.8–6.8 times in regenerants. The negative effect of excess cadmium in the soil on the accumulation of zinc in barley was shown. There was no gradation in the importance of organs for zinc accumulation or any presence of functional barriers preventing this. Regenerants induced on selective media with cadmium had the greatest adaptive advantages to stress: pronounced barrier functions of roots, minimal accumulation of toxic ions in aerial organs, and high seed productivity (they exceeded the original genotype by 35.5%). Adaptive reactions associated with the limitation of cadmium accumulation in plant tissues of regenerants, obtained by in vitro selections with aluminum and an osmotic, were shown to be weak.